2021
DOI: 10.18488/journal.61.2021.91.128.140
|View full text |Cite
|
Sign up to set email alerts
|

Critical Review on Flipped Classroom Model Versus Traditional Lecture Method

Abstract: Contribution/Originality: This study makes a critical review of 33 studies on Flipped classroom model with the view to understand how the previous studies have acknowledge the importance, adaptability and of flipped classroom model in the modern learning environments and also how they differentiated this model from the Traditional Lecture Method. INTRODUCTIONLearning is an essential element of humankind and crucial for the development of a nation (Hafeez et al., 2020). Buckman et al. (2010) stated that there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…Regarding academic performance on English writing in the research, flipped classroom can increase students' writing even though with slightly change. The exploration on the effective work of FC is still need to do as previous research suggested (Erbil, 2020;Rasheed et al, 2020;Saira et al, 2021;Turan & Akdag-Cimen, 2020). Flipped classroom can ease the teaching of writing if it is wellexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding academic performance on English writing in the research, flipped classroom can increase students' writing even though with slightly change. The exploration on the effective work of FC is still need to do as previous research suggested (Erbil, 2020;Rasheed et al, 2020;Saira et al, 2021;Turan & Akdag-Cimen, 2020). Flipped classroom can ease the teaching of writing if it is wellexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The flipped classroom is an example of the blended learning approach. In a flipped classroom model, traditional lecture and homework elements are reversed (Yavuz & Ozdemir, 2019;Ajmal & Hafeez, 2021). Students engage with prerecorded video lectures or online resources at home, and class time is dedicated to hands-on activities, discussions, and problem-solving.…”
Section: The Types Of Blended Learning In Stem Educationmentioning
confidence: 99%
“…Hasil validasi menunjukkan bahwa bahan ajar yang dikembangkan dapat dipergunakan dengan mudah oleh peserta didik kelas tujuh. Para validator memberikan penilaian sangat baik yang menunjukkan bahwa bahan ajar tersebut mudah dipergunakan oleh siswa, hal ini disebabkan karena bahan ajar tersebut menggunakan kearifan lokal dan potensi lokal yang telah dikenal, diketahui dan ditemui dalam kehidupan sehari-hari siswa (Khusniati, Parmin, and Sudarmin, 2017;Saira, Ajmal, and Hafeez, 2021).…”
Section: Pembahasanunclassified